Migrating Towards Growth and Oblivion? A Contextual Account of the Lives and Work of Spanish-Mexican Composers María Teresa Prieto and Emiliana de Zubeldía - Chibici-Revneanu, Claudia Christina (Revista Interdisciplinaria de Estudios de Género de El Colegio de México, 2020)
Drawing from an interdisciplinary methodology which brings together feminist musicology, gender, and migration, as well as cultural studies, this article focuses on the lives and works of 20th-century Spanish-Mexican composers María Teresa Prieto and Emiliana de Zubeldía. It aims to analyze their biographies within the context of the frequent under-representation of women in discussions about migration and music. It will show how geographical displacement enhanced their creative development and careers by allowing them to develop broad networks, giving them enriched processes of cultural transfer, involving them in rival national/regional identity claims, and liberating them from restrictive (musical) gender norms. Nevertheless, their contextual advantages proved insufficient in the face of more powerful gender-discriminatory structures within the musical sphere, which have typically truncated musical women’s journeys by oblivion.